Antithrombotic and Anticoagulant Activities of a Low Molecular Weight Fucoidan by the Subcutaneous Route - Millet, J.; Jouault, S. Colliec; Mauray, S.; Theveniaux, J.; Sternberg, C.; Vidal, Boisson C.; Fischer, A. M. (Thrombosis and Haemostasis, 1999)
Fucoidans (high-molecular-weight sulfated polysaccharides extracted from brown seaweeds) have anticoagulant and antithrombotic effects. They inhibit thrombin by catalyzing both serpins (antithrombin and heparin cofactor II) according to their chemical structures and origins. In this study, a low-molecular-weight (LMW) fucoidan of 8 kDa was obtained by chemical degradation of a high-molecular-weight fraction. The antithrombotic and anticoagulant activities of this new compound were compared to those of a low-molecular-weight heparin (LMWH), dalteparin, following subcutaneous administration to rabbits. This LMW fucoidan exhibited dose-related venous antithrombotic activity, with an ED80 of about 20 mg/kg, 2 h after a single subcutaneous injection. Its activity was comparable to that of dalteparin (close to 200 anti-Xa IU/kg) and was maximal 30 min after a single subcutaneous injection. The activity remained stable (about 70%) from 1 to 4 h after injection, but disappeared by 8 h. The antithrombotic activity was not associated with either a prolongation of the thrombin clotting time (TCT) or an increase in anti-Xa activity, contrary to dalteparin. A slight prolongation of APTT occurred with both compounds. This venous antithrombotic activity was associated with a decrease in ex vivo thrombin generation and with a significant increase in the lag phase in a thrombin generation test. LMW fucoidan thus has potent antithrombotic activity and a potentially weaker haemorrhagic effect (i.e. a smaller effect on coagulation tests and a smaller prolongation of the bleeding time) than dalteparin.